Source pools and disharmony of the world's island floras. Issue 1 (22nd September 2020) - König, Christian; Weigelt, Patrick; Taylor, Amanda; Stein, Anke; Dawson, Wayne; Essl, Franz; Pergl, Jan; Pyšek, Petr; van Kleunen, Mark; Winter, Marten; Chatelain, Cyrille; Wieringa, Jan J.; et al.
Abstract : Island disharmony refers to the biased representation of higher taxa on islands compared to their mainland source regions and represents a central concept in island biology. Here, we develop a generalizable framework for approximating these source regions and conduct the first global assessment of island disharmony and its underlying drivers. We compiled vascular plant species lists for 178 oceanic islands and 735 mainland regions. Using mainland data only, we modelled species turnover as a function of environmental and geographic distance and predicted the proportion of shared species between each island and mainland region. We then quantified the over‐ or under‐representation of families on individual islands (representational disharmony) by contrasting the observed number of species against a null model of random colonization from the mainland source pool, and analysed the effects of six family‐level functional traits on the resulting measure. Furthermore, we aggregated the values of representational disharmony per island to characterize overall taxonomic bias of a given flora (compositional disharmony), and analysed this second measure as a function of four island biogeographical variables. Our results indicate considerable variation in representational disharmony both within and among plant families. Examples of generally over‐represented families include Urticaceae, Convolvulaceae and almost all pteridophyte families. Other families such as Asteraceae and Orchidaceae were generally under‐represented, with local peaks of over‐representation in known radiation hotspots. Abiotic pollination and a lack of dispersal specialization were most strongly associated with an insular over‐representation of families, whereas other family‐level traits showed minor effects. With respect to compositional disharmony, large, high‐elevation islands tended to have the most disharmonic floras. Our results provide important insights into the taxon‐ and island‐specific drivers of disharmony. The proposed framework allows overcoming the limitations of previous approaches and provides a quantitative basis for incorporating functional and phylogenetic approaches into future studies of island disharmony.